2017
DOI: 10.1155/2017/2850947
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and Anti‐Inflammatory Activities of Houttuynia cordata Decoction for Oral Care

Abstract: Dental biofilms that form in the oral cavity play a critical role in the pathogenesis of several infectious oral diseases, including dental caries, periodontal disease, and oral candidiasis. Houttuynia cordata (HC, Saururaceae) is a widely used traditional medicine, for both internal and external application. A decoction of dried HC leaves (dHC) has long been consumed as a health-promoting herbal tea in Japan. We have recently reported that a water solution of HC poultice ethanol extract (wHCP) exerts antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Further insight into antibiofilm potential of quercetin has been provided in the study by Gao et al [18] where it was observed that treatment with this flavonoid leads to reduced ALS1, ALS3 (Agglutinin Like Sequence gene family), HWP1 (Hyphal Wall Protein), and SUN41 (gene encoding for secreted beta-glucosidase) expression levels. Quercitrin had the lowest potential to reduce biofilm formation among all the flavonoids tested in our study ( Figure 1) with its complete lack of activity towards C. albicans CAD1 biofilm observed previously [19]. On the other hand, excellent activity on inhibition of C. albicans biofilm formation was addressed to another flavonol glycoside, isoquercitrin (tested concentration 9.38-37.5 µg/mL) ( Figure 1) with a previous study [19] highlighting its antibiofilm potential in higher concentration-200 µg/mL.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Further insight into antibiofilm potential of quercetin has been provided in the study by Gao et al [18] where it was observed that treatment with this flavonoid leads to reduced ALS1, ALS3 (Agglutinin Like Sequence gene family), HWP1 (Hyphal Wall Protein), and SUN41 (gene encoding for secreted beta-glucosidase) expression levels. Quercitrin had the lowest potential to reduce biofilm formation among all the flavonoids tested in our study ( Figure 1) with its complete lack of activity towards C. albicans CAD1 biofilm observed previously [19]. On the other hand, excellent activity on inhibition of C. albicans biofilm formation was addressed to another flavonol glycoside, isoquercitrin (tested concentration 9.38-37.5 µg/mL) ( Figure 1) with a previous study [19] highlighting its antibiofilm potential in higher concentration-200 µg/mL.…”
Section: Discussionsupporting
confidence: 49%
“…Quercitrin had the lowest potential to reduce biofilm formation among all the flavonoids tested in our study ( Figure 1) with its complete lack of activity towards C. albicans CAD1 biofilm observed previously [19]. On the other hand, excellent activity on inhibition of C. albicans biofilm formation was addressed to another flavonol glycoside, isoquercitrin (tested concentration 9.38-37.5 µg/mL) ( Figure 1) with a previous study [19] highlighting its antibiofilm potential in higher concentration-200 µg/mL. Rutin was among the natural compounds with the lowest activity against biofilm formation in this study (Figure 1) with its lack of C. albicans CAD1 antibiofilm activity also observed earlier [19].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Herbal teas provide relief for pharyngeal inflammation in patients with streptococcal pharyngitis. Anti-inflammatory activities of herbal extracts and infusions have been shown by several authors previously [55,56]. Our recently published data on anti-inflammatory properties of these extracts have proven the ability of all four efficacious HWIs for suppression of pro-inflammatory cytokines released from inflamed human tonsil epithelial cells (HTonEpiCs) induced by antigens (lipoteichoic acid and peptidoglycan) of S. pyogenes [8].…”
Section: Discussionmentioning
confidence: 89%
“…A number of published reports over the past few years hypothesized the extracts of Houttuynia cordata to be one of the therapeutic possibilities of HSV-1 infection. H. cordata , also named “Yu-xing-cao”, is a vegetable crop and has been used widely as an effective TCM for hundreds of years due to its anti-inflammatory [ 64 , 65 ] and antiviral [ 42 , 46 , 50 ] activities.…”
Section: Natural Anti-hsv-1 Products From Tcmmentioning
confidence: 99%